The topography of the city of Barcelona and its urban context in eastern Catalonia: from the third to the twelfth centuries - Banks, Philip J. (1981)
Among the Roman foundations in modern Catalonia was the colonia of Barcino, which, unlike several of its neighbours, had no local native predecessor. The growth of these cities was slow, and an air of mediocrity shrouds them all, save Tarraco. With the decline of nearby communities in the third century, the significance of Barcino increased. New defences and economic activity, supplemented by the presence of civil and ecclesiastical powers in the Visigothic period, ensured the survival of urban life, although a tendency to contraction around the religious centre is apparent in the topography of the 6th. century, marking the beginning of the transition to the medieval plan.